2008
DOI: 10.1002/pssc.200779226
|View full text |Cite
|
Sign up to set email alerts
|

Effect of c‐plane sapphire misorientation on the growth of AlN by high‐temperature MOVPE

Abstract: AlN layers were directly grown on sapphire substrates with slightly different miscut angles from the c‐plane by metalorganic vapor phase epitaxy at 1300 °C. By X‐ray diffraction analysis, the structural quality was found to improve with the increase in substrate off‐angle. When the substrate off‐angle was 0.5°, the X‐ray rocking curve (XRC) full widths at half maximum (FWHMs) of symmetric and asymmetric planes were 170 and 550 arcsec, respectively. At smaller off‐angle, XRC‐FWHMs were wider. When the substrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2009
2009
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 10 publications
2
24
0
Order By: Relevance
“…The surface energy changes very slowly with a large deviation in λ s due to the exponential in Equation 17, helping to validate the use of the calculated γ s value. According to these results, the surface energy of the Al-polar surface of AlN is of the same order of magnitude as that of the (1-100) and (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) planes, which were predicted from density functional theory by Jindal et al to be 175 and 187 meV/Å 2 , respectively. 29 Furthermore, this result can be used to corroborate current theoretical models that try to predict the surface energy.…”
Section: B Aln Homoepitaxial Growthmentioning
confidence: 55%
See 3 more Smart Citations
“…The surface energy changes very slowly with a large deviation in λ s due to the exponential in Equation 17, helping to validate the use of the calculated γ s value. According to these results, the surface energy of the Al-polar surface of AlN is of the same order of magnitude as that of the (1-100) and (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) planes, which were predicted from density functional theory by Jindal et al to be 175 and 187 meV/Å 2 , respectively. 29 Furthermore, this result can be used to corroborate current theoretical models that try to predict the surface energy.…”
Section: B Aln Homoepitaxial Growthmentioning
confidence: 55%
“…All of these general trends were found to be independent of the misorientation direction. The only differences observed for misorientations toward [1-100] as compared to [11][12][13][14][15][16][17][18][19][20] was the step edge shape, as discussed earlier and depicted in Figure 1.…”
Section: B Aln Homoepitaxial Growthmentioning
confidence: 76%
See 2 more Smart Citations
“…The use of off-cut sapphire has been found to be very effective in growing highquality a-plane GaN [10] and c-plane AlN [11] with a fairly flat surface. Shibata et al [12] reported the effect of the misorientation of r-plane sapphire on the crystalline quality of AlN.…”
Section: Introductionmentioning
confidence: 99%